2015
DOI: 10.4236/ijohns.2015.46068
|View full text |Cite
|
Sign up to set email alerts
|

Plexiform Neurofibroma of Nasal Tip

Abstract: Neurogenic tumor is the name given to any tumor that arises from the nerve tissue or its coverings. Neurogenic tumors of Sino-nasal cavity are a very rare entity. The most common types are Schwannomas and Neurofibromas and the plexiform subtype is one form of these neuroendocrine tumors. We report the case series of two such cases of a plexiform neurofibroma of the nasal tip, which were excised via an open rhinoplasty approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…35 The deeper, infiltrative portion is diffusely hypoechoic, in contrast to subcutaneous tissue. 33 In this review, four patients (30.76 per cent) underwent biopsy before definitive surgery, 3,15,17 and the results were inconclusive. Biopsy findings may indicate the benign neurogenic nature of the tumour; however, a definitive diagnosis cannot often be reached.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…35 The deeper, infiltrative portion is diffusely hypoechoic, in contrast to subcutaneous tissue. 33 In this review, four patients (30.76 per cent) underwent biopsy before definitive surgery, 3,15,17 and the results were inconclusive. Biopsy findings may indicate the benign neurogenic nature of the tumour; however, a definitive diagnosis cannot often be reached.…”
Section: Discussionmentioning
confidence: 83%
“…18 Involvement of the nasal tip 3,15,17 was identified in three patients in this review, for which the treatment remains more challenging because of its prominent position, thick and less flexible skin, more sebaceous glands, and consequent higher chance of recurrence. 15,48,51–54 Bartolo et al . found that even after surgery, the nasal tip may stay bulky and need revision surgery.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations